Layout of Gokarneshwara Mahadeva Temple - Temples of India Project Team (Jio Institute, 2024)
The layout of Gokarneshwara Mahadeva shrine as drawn by A.C.L. Carlleyle, and he described the shrine as ‘…a cave temple, or rather a cave, in which temples or shrines have been built, within a two-storied screen or facing of masonry in the face of the rock, in the side of the mountain at the entrance to the pass, immediately opposite to the town of Visalpur… But apart from the bases of some of the pillars (which appear to be older than the rest), the whole of the structures in the cave appear to be modern…’